Impact of Ontology-Based Service-Oriented Ecosystems on the Digital Transformation of Railway Transport and Engineering Education. - Alves, Arian (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2024)
The digital transformation of industries is one of the most pressing topics in contemporary research, and the railway transport sector is no exception. As a key player in the transportation sector, railways are undergoing significant changes due to the advancement of digital technologies. One of the critical approaches to this transformation is the adoption of ontology-based service-oriented ecosystems (OBSOEs). This paper explores the impact of OBSOEs on the digital transformation of railway transport and engineering education, focusing on how ontologies and serviceoriented architectures (SOA) can streamline operations, enhance interoperability, and optimize the learning processes in educational institutions. The paper also delves into the benefits, challenges, and future directions of using OBSOEs in both domains.